2013
DOI: 10.1371/journal.pone.0061644
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of Self-Initiated, Event-Driven Infectious Disease Reporting in General Population Cohorts

Abstract: BackgroundThe 2009/2010 pandemic influenza highlighted the need for valid and timely incidence data. In 2007 we started the development of a passive surveillance scheme based on passive follow-up of representative general population cohorts. Cohort members are asked to spontaneously report all instances of colds and fevers as soon as they occur for up to 9 months. Suspecting that compliance might be poor, we aimed to assess the validity of self-initiated, event-driven outcome reporting over long periods.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…While we lack a formal validation against a gold-standard method, we argue for the validity of our results based on a number of separate lines of evidence. With regard to self-reporting of ILI/ acute respiratory infection (ARI), the framework for self-initiated, eventdriven infectious disease reporting that we employed had already been developed for a Swedish population-based cohort [8] and used for population-based surveillance in Stockholm County since 2007 [16]. A separate validation study concluded that while there was significant under-reporting of disease (estimated at 60%), this level of under-reporting was remarkably constant over time and across seasons [16], so that a simple constant correction factor can potentially restore validity of incidence rates, at least in terms of reported disease incidence.…”
Section: Discussionmentioning
confidence: 99%
“…While we lack a formal validation against a gold-standard method, we argue for the validity of our results based on a number of separate lines of evidence. With regard to self-reporting of ILI/ acute respiratory infection (ARI), the framework for self-initiated, eventdriven infectious disease reporting that we employed had already been developed for a Swedish population-based cohort [8] and used for population-based surveillance in Stockholm County since 2007 [16]. A separate validation study concluded that while there was significant under-reporting of disease (estimated at 60%), this level of under-reporting was remarkably constant over time and across seasons [16], so that a simple constant correction factor can potentially restore validity of incidence rates, at least in terms of reported disease incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Underreporting that is non-differential vis-à-vis the explanatory variables will not bias the risk-ratio estimate if the proportion with false positive reports is negligible [27]. A previous validation study confirmed that the false positive reporting is indeed insignificant [17], but we cannot exclude the possibility that the underreporting was differential, i.e. that participants who washed their hands frequently were more prone to report disease to the surveillance system.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, new approaches in syndromic surveillance -the collection and interpretation of data for public health before laboratory or clinical confirmation is available (Lazarus et al, 2001;Mandl et al, 2004) -have emerged. Several systems are in evaluation, showing a large diversity of data sources and methodologies employed, such as telephone-based health information services (Cooper et al, 2008), automated medical records (Lazarus et al, 2001;van den Wijngaard et al, 2008), pharmacy sales and absenteeism (Chretien et al, 2008), queries to online search engines (Ginsberg et al, 2009), and telephone-based self-reporting in cohorts of randomly selected participants (Merk et al, 2013;Rehn et al, 2014). Syndromic surveillance is complementary to traditional public health surveillance in disease reporting (Henning, 2004;Lipsitch et al, 2009).…”
Section: Introductionmentioning
confidence: 99%